2008
DOI: 10.1021/ja711167v
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Reactivity of D3h C78 (Metallo)Fullerene: Regioselectivity Changes Induced by Sc3N Encapsulation

Abstract: We report here for the first time a full comparison of the exohedral reactivity of a given fullerene and its parent trinitride template endohedral metallofullerene. In particular, we study the thermodynamics and kinetics for the Diels-Alder [4 + 2] cycloaddition between 1,3-butadiene and free D3h'-C78 fullerene and between butadiene and the corresponding endohedral D3h-Sc3N@C78 derivative. The reaction is studied for all nonequivalent bonds, in both the free and the endohedral fullerenes, at the BP86/TZP//BP86… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
105
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(112 citation statements)
references
References 39 publications
7
105
0
Order By: Relevance
“…Cycloaddition reactions of fullerene and its derivatives have been analyzed by considerations of bond lengths and orbital coefficients. [94,95] Short bond distances together with high pyramidalization angles are usually considered to be the most important structural parameters related to fullerene reactivity. On the other hand, low-lying unoccupied orbitals that present suitable energy and shape to interact are also required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cycloaddition reactions of fullerene and its derivatives have been analyzed by considerations of bond lengths and orbital coefficients. [94,95] Short bond distances together with high pyramidalization angles are usually considered to be the most important structural parameters related to fullerene reactivity. On the other hand, low-lying unoccupied orbitals that present suitable energy and shape to interact are also required.…”
Section: Discussionmentioning
confidence: 99%
“…There are some cases where the previously mentioned parameters to understand cycloaddition reactions give contradictory predictions. The most pyramidalized bonds do not always lead to the most favorable addition; [94] those bonds with extremely long carbon distances can also be reactive. [95] Moreover, the predictions of reactivity from the LUMOs are qualitatively correct, but they are much too imprecise in the sense that one finds many bonds with suitable orbitals for the interaction with a diene or a 1,3-dipole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, we cannot compare our results with the monoadduct of Sc 3 N@D 5h -C 80 synthetized via a 1,3-dipolar cycloaddition 25,26 or to those calculated for the Diels-Alder additions, [36][37][38] because it has been shown that for endohedral fullerenes different reaction types yield different regioisomers. For example, 1,3-dipolar cycloadditions on Sc 3 N@I h -C 80 result in addition to [5,6]-bonds as the thermodynamic product, 39,40 while cyclopropanation reactions typically results in additions to [6,6]-bonds, 17 with only one exception reported.…”
mentioning
confidence: 90%
“…The metal-cage and intracluster bonding in endohedral metallofullerenes encapsulating among others La 2 and triangular La 3 N templates was studied in detail by quantum theory of atoms in molecules method. 38 Very recently 39,40 Osuna et al reported a full comparison of the exohedral reactivity of a given fullerene and its parent trinitride template endohedral metallofullerene. In particular, they studied the thermodynamics and kinetics for the Diels-Alder [4 1 2] cycloaddition between 1,3-butadiene and free D 3h -C 78 fullerene and between butadiene and the corresponding endohedral D 3h -Sc 3 N@C 78 and D 3h -Y 3 N@C 78 derivatives at the BP86/TZP//BP86/DZP level of theory.…”
Section: Introductionmentioning
confidence: 99%